ASPEK SOSIO-KULTURAL DALAM KITAB-KITAB FIKIH - Ambo, Rahman (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
This article outlines the aspects of socio-culturan problems in the books fikhi. From the discussion, it is understood that the concept of Islamic law reform must be based on the spirit to ground within the framework of the implementation of Islamic law through legislation and regulation. Therefore, the use of the methodology and multidisciplinary approach in establishing a very urgent law to be held. With the elaboration of classical methodologies and modern scientific approach will produce an objective study of jurisprudence, humane, and progressive. Due to advances in science and technological and globalization that swept the world today implicates the changes in social life. Changes that occur in a variety of fields, so it is certain that the social conditions also change with the level of thought patterns that develop. Law so that it can be because it is influenced by, the influence of foreign cultures, saturation of the system is established, and the level of belief against the law increasingly. There are many factors that affect birth of fiqh. The aspects that are directly related to the life of the clergy, so that it has relevance in shaping their thinking horizons. Aspects that include; a ) Political Aspects, b ) Cultural Aspects , 3 ) Social Aspects of social